RNA Isolation from Oral Swab Sample On Bats of Rural Area, Braja Harjosari, East Lampung - Kurniasih, Vidyanti; Rustiati, Elly Lestari; Priyambodo, Priyambodo; Srihanto, Eko Agus; Saswiyanti, Enny; Pratiwi, Dian Neli (Ann Publisher, 2026)
Background. Bats are considered animals that carry infectious diseases, are known to be reservoirs of viruses, and are suspected of causing disease outbreaks. The World Health Organization stated that this disease outbreak is caused by Coronavirus Disease 2019 (COVID-19), which is caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Aims. Under the Research Innovation and Collaboration Program - Higher Education for Technology and Innovation Project (HETI) and in collaboration with the Lampung Disease Investigation Center, a preliminary study on EID detection on bats based on Predict Protocols was done to identify the presence of coronavirus on bats, including rural areas, Braja Harjosari, East Lampung. It is located next to Way Kambas National Park. Methods. Oral swab samples were taken from ten bats, 3 species: Cynopterus brachyotis and Cynopterus horsfieldi, and Scotophilus kuhlii. RNA extraction was conducted by Predict Protocols, which has four stages: lysis, binding, washing, and elution. Conclusion. Two samples showed thin-band luminescence. While in the quantity test, there are three samples of good concentration results between 1.8 and 2.0.